HUBUNGAN KADAR HIGH DENSITY LIPOPROTEIN (HDL) TERHADAP GLUKOSA DARAH SEWAKTU PADA PENDERITA DIABETES MELLITUS DI RS BENYAMIN GULUH KOLAKA - Nurul Afdhaliyah Nurdin; Alma Dita Harun; Suci Devianti Ningsih; Niluh Eka Ayu Pratiwi (Program Study of Medical Laboratory Technology , Politeknik Bina Husada Kendari, 2022)
Diabetes Mellitus (DM) is a very common health problem. Diabetes mellitus is a chronic disease that generally affects throughout the life of the patient and requires long-term treatment, in addition to the state of insulin resistance or metabolic syndrome and Diabetes Mellitus (DM) cause’s lipid metabolic abnormalities characterized by an increase or decrease in lipid fraction. Increased cholesterol High Density Lipoprotein (HDL) can reduce the risk of atorosclerosis. Besides that, the HDL function is as the main means of transporting excess cholesterol from extra hepatic tissue and cleaning cells then to be released through the bile. This study aims to determine the relationship between of the High Density Lipoprotein (HDL) levels to blood glucose to the patients' of diabetes mellitus at Benyamin Guluh Hospital in Kolaka. The type of this study is analytic observational with the sampling technique of Accidental Sampling and 30 people of total samples. The results of this study showed that there was no relationship between HDL levels and blood glucose. This could be seen in the p-value of 0.107 and the r value of 0.300. Keywords : High Density Lipoprotein (HDL), Diabetes Mellitus (DM)